An Analysis of Inflectional and Derivational Affixes of the Students’ Academic Writing - Stanislaus Guna,; Irene Nindiana Lehon,; Maksimilianus Sapong,; Angelus Rico Sambora,; Yohanes Tresno Kurnianto, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study investigates the use of inflectional and derivational affixes in the academic writing of second–year English students, identifying the challenges they face in applying these linguistic elements. Using qualitative methods, specifically content analysis, this study examined a sample of 30 students' writings from the 2021C class. The analysis identified a total of 172 affixes: 122 inflectional suffixes, 36 derivational suffixes, and 14 derivational prefixes. Inflectional suffixes, particularly irregular forms, were predominantly used, while derivational affixes primarily served to change grammatical classes, with "–ly" being the most common. Students encountered several challenges, such as errors in inflectional suffix usage (e.g., omission of plural markers and subject–verb agreement issues) and difficulties with derivational affixes (e.g., omissions and incorrect usage of "–ing," "–ment," "–able," "–re," "–un"). These problems were attributed to confusion between bound and free morphemes, forgetfulness, and a lack of awareness. The study recommends tailored teaching strategies, including targeted exercises, detailed explanations, and ample practice opportunities, to improve students' proficiency with affixes, thereby enhancing the quality and clarity of their academic writing